Analisis Sistem Keamanan Wireless Local Area Network (WLAN) Pada Proses Tethering - Kurniawan, M. R.; Sari, Linna Oktaviana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Various types of technology facilities currently continue to develop in various ways, network security needs to be considered as the technology facilities develop. Tethering is a technology facility that is widely used today, such as in office areas, homes, boarding houses and campuses. In analyzing network security when using tethering as a media connection to the internet, testing and analysis are carried out when the test results are obtained. The testing techniques used are sniffing and scanning using inSSIDer home software, kismet, and aircrack-ng and airodump-ng tools. The results obtained from this test are that the inSSIDer and kismet software get open or encrypted security, then aircrak and airodump-ng can find the password used by Access Point (AP) tethering. From the tests carried out it can be concluded that the security of WLAN networks when using tethering is still categorized as not safe.Keyword: Wireless Local Area Network (WLAN), tethering, aircrack-ng, airodump-ng, inSSIDer, kismet.